The Effect of an Intravenous Infusion E-material on the Second Year Nursing Students’ Ability to Demonstrate the Procedure of Intravenous Infusion - Chatchaisucha, Sirirat; Jitramontree, Narirat; Vanicharoenchai, Vorawan (Nursing Science Journal of Thailand, 2011)
Purposes: To compare the nursing students’ ability todemonstrate the procedure of intravenous infusion between anexperimental group learning through intravenous infusione-material and a control group learning through usual methods ofdemonstration and return-demonstration, and to assess thesatisfaction of using the intravenous infusion e-material. Design: Quasi-experimental research design. Methods: The sample was the bachelor degree second yearnursing students at the Faculty of Nursing, Mahidol Universitywith a total number of 135. All participants were simple randomlyassigned to the control group (n = 71) and the experimental group(n = 64). Data were collected by using a procedure checklist and asatisfaction questionnaire. Descriptive statistics (mean, standarddeviation) and t-test were used for data analysis. Main findings: Significantly, the experimental group showedhigher competency (p < .01) in demonstrating the procedure ofintravenous infusion than did the control group. The participantsin the experimental group were also satisfied with usingintravenous infusion e-material at a high level. Conclusion and recommendations: Using the intravenousinfusion e-material is very useful for the nursing students. Thestudents are able to study at their own convenience and as often asneeded till their ability being developed. The e-material, therefore,is a very significant tool in improving quality of education.